Ähnlichkeitsbasierte Suche in Geschäftsprozessmodelldatenbanken - Schoknecht, Andreas (KIT Scientific Publishing, 2018)
The reuse of process models is a promising technique to reduce modelling effort. Yet, finding similar models in large model collections is not feasible manually. A search functionality for relevant models, which can be used as a template, is therefore helpful. This work describes multiple techniques for finding similar process models and acitvities in process model repositories.